2022
DOI: 10.3389/fgene.2022.984158
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-Related genes in the prognosis of colorectal cancer and their correlation with the tumor microenvironment

Abstract: Colorectal cancer (CRC) is a common tumor disease of the digestive system with high incidence and mortality. Cuproptosis has recently been found to be a new form of cell death. The clinical significance of cuproptosis-related genes (CRGs) in CRC is not clear. In this study, The Cancer Genome Atlas Colon and Rectal Cancer dataset was used to analyze the relationship between CRGs and clinical characteristics of CRC by differential expression analysis and Kaplan–Meier survival (K-M) analysis. Based on CRGs, progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recently, several papers have been published on the use of a model based on cuproptosis-associated genes for predicting prognosis (32)(33)(34)(35). However, these papers suffer from several limitations, including a small number of genes in their signature, relatively low prognostic power, and illogical combination with other cell death types like ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several papers have been published on the use of a model based on cuproptosis-associated genes for predicting prognosis (32)(33)(34)(35). However, these papers suffer from several limitations, including a small number of genes in their signature, relatively low prognostic power, and illogical combination with other cell death types like ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The value of CRGs in patients with COAD was further corroborated in related articles. In Wu's study, 53 they established a model using multivariate Cox regression analysis and constructed a prognostic risk score accordingly and the clinical and immunological differences in patients with different risk scores were further investigated. Similarly in Xu's study, 54 they screened out the modeled genes from clustering results which were based on CRGs, and a total of 11 genes were finally generated.…”
Section: Discussionmentioning
confidence: 99%
“…Lower CRIRS, contrarily, suggested a more favorable response to chemotherapy/targeted drugs and immunotherapy [182]. Moreover, several studies established the CRG risk score signature based on cuproptosis-associated gene expression and confirmed that the CRG risk score is a strong prognostic marker and could contribute to guiding more effective treatment regimens [183][184][185][186]. Compared with a single gene expression level, this risk scoreassociated assessment based on machine deep learning is more accurate in reflecting the role of cuproptosis in tumorigenesis and treatment because cuproptosis is a multiplegene-regulated biological process.…”
Section: Scores Based On Cuproptosis-related Genesmentioning
confidence: 96%